(untitled) (Revista Electrónica REDINE, 2018)
PowerPoint, tool that allows to create presentations and this way to communicate information and ideas of visual and attractive form. The teacher can use presentations as support to the education and this way expose information of visual, agreeable form and catch the attention of the pupil. With the intention of facilitating and improving the process of education learning of the medical basic sciences, in what concerns the histology, there was constructed an atlas of oral histology, with updated information, to be used by students of odontolgy and medicine.